Applications of Computational Intelligence in Biomedical Technology - Bris, Radim; Majernik, Jaroslav; Pancerz, Krzysztof; Zaitseva, Elena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents latest results and selected applications of Computational Intelligence in Biomedical Technologies. Most of contributions deal with problems of Biomedical and Medical Informatics, ranging from theoretical considerations to practical applications. Various aspects of development methods and algorithms in Biomedical and Medical Informatics as well as Algorithms for medical image processing, modeling methods are discussed. Individual contributions also cover medical decision making support, estimation of risks of treatments, reliability of medical systems, problems of practical clinical applications and many other topics  This book is intended for scientists interested in problems of Biomedical Technologies, for researchers and academic staff, for all dealing with Biomedical and Medical Informatics, as well as PhD students. Useful information is offered also to IT companies, developers of equipment and/or software for medicine and medical professionals.  .
Mesh-based Modeling of Individual Cells and their Dynamics in Biological Fluids -- Usage of Industrial Computed Tomography for Evaluation of Custom-Made Implants -- Assessment of Mortality Risk for Patients Undergoing Colorectal Surgery Using Regression Modelling -- Profiling of Software Requirements for the Pharmaceutical Enterprise Manufacturing Execution System -- Application of Survival Analysis on Analysing the Association between Chromosomal Aberrations and Carcinoma -- Modelling the Results of the Phadiatop Test Using the Logistic and Ordinal Regression -- Complex Data Management in MRI Results Processing -- Biometrics for Biomedical Applications -- Multimedia Support of Medical Education Utilizing On-Line Archive of Video Lectures -- Evaluation of Postural Stability Using Motion Analysis Techniques -- Some Issues on an Object-Oriented Programming Language  for Physarum Machines -- A Tool for Computer-Aided Diagnosis of Psychological Disorders Based on the MMPI Test: an Overview -- The Instance and Feature Selection for Neural Network Based Diagnosis of Chronic Obstructive Bronchitis -- New Methods for the Reliability Analysis of Healthcare System Based on Application of Multi-State System.
Keywords: Computational intelligence; Biomedical engineering; Artificial intelligence; Computational Intelligence; Biomedical Engineering and Bioengineering; Artificial Intelligence